2011
DOI: 10.3109/02699206.2011.570852
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Bilingual Aphasia Test for assessment and transcranial direct current stimulation to modulate language acquisition in minimally verbal children with autism

Abstract: Minimally verbal children with autism commonly demonstrate language dysfunction, including immature syntax acquisition. We hypothesised that transcranial direct current stimulation (tDCS) should facilitate language acquisition in a cohort (n = 10) of children with immature syntax. We modified the English version of the Bilingual Aphasia Test (BAT) to test only basic canonical subject-verb-object sentences. We tested syntactic accuracy after teaching then testing all vocabulary from the subsequent syntax test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 43 publications
1
81
0
Order By: Relevance
“…Neuroanatomical and functional studies point to an alteration of synaptic maturation and cortical connectivity during early neurodevelopment, leading to a thinner cortical gray matter and alterations of frontal lobe connections, which may explain the different clinical manifestations (Courchesne and Pierce, 2005). From a theoretical point of view, noninvasive brain stimulation could be a useful way to modulate possible cortical mechanisms of this disorder and its functional effects (Schneider and Hopp, 2011). In children aged between 5 and 8 years, specific improvements in the scores of the Autism Treatment Evaluation Checklist and Children's Global Assessment Scale, but not in the Childhood Autism Rating Scale, were described after five consecutive sessions of anodal tDCS applied over the left dorsolateral prefrontal cortex (1 mA for 20 min), with the cathode placed on the right contralateral shoulder, when compared to sham stimulation (Amatachaya et al, 2014).…”
Section: Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroanatomical and functional studies point to an alteration of synaptic maturation and cortical connectivity during early neurodevelopment, leading to a thinner cortical gray matter and alterations of frontal lobe connections, which may explain the different clinical manifestations (Courchesne and Pierce, 2005). From a theoretical point of view, noninvasive brain stimulation could be a useful way to modulate possible cortical mechanisms of this disorder and its functional effects (Schneider and Hopp, 2011). In children aged between 5 and 8 years, specific improvements in the scores of the Autism Treatment Evaluation Checklist and Children's Global Assessment Scale, but not in the Childhood Autism Rating Scale, were described after five consecutive sessions of anodal tDCS applied over the left dorsolateral prefrontal cortex (1 mA for 20 min), with the cathode placed on the right contralateral shoulder, when compared to sham stimulation (Amatachaya et al, 2014).…”
Section: Autismmentioning
confidence: 99%
“…In children aged between 5 and 8 years, specific improvements in the scores of the Autism Treatment Evaluation Checklist and Children's Global Assessment Scale, but not in the Childhood Autism Rating Scale, were described after five consecutive sessions of anodal tDCS applied over the left dorsolateral prefrontal cortex (1 mA for 20 min), with the cathode placed on the right contralateral shoulder, when compared to sham stimulation (Amatachaya et al, 2014). Prefrontal stimulation was conducted to modulate language and cognitive functions, in which the prefrontal cortex is involved (Schneider and Hopp, 2011). With the same stimulation protocol, but applied in two single sessions of anodal tDCS separated by 1 week, improvements in the social scale and health and behavioral problems scale of the Autism Treatment Evaluation Checklist (but not in the language scale nor the sensory and cognitive awareness scale) and peak alpha EEG power have been described in children with the same age range ( Amatachaya et al, 2015).…”
Section: Autismmentioning
confidence: 99%
“…Boggio, Sultani, and colleagues (2008) Other Clinical Cases. Schneider and Hopp (2011) found improved language (syntax) acquisition in a group of children with autism after a single 30-min tDCS session, with anodal stimulation over the left DLPFC. Vercammen et al (2011) found increased variability in performance on a probabilistic association learning task, after 20 min of anodal stimulation of the left DLPFC, in a group of patients with schizophrenia and suggested that this may imply beneficial effects in a subgroup of these patients.…”
Section: The Dorsolateral Prefrontal Cortexmentioning
confidence: 99%
“…An open study evaluating autistic patients with minimal verbal language have applied anodal tDCS over the Broca's area to improve language acquisition and the results showed that mean vocabulary scores were significantly higher after the intervention Schneider et al [104] . One double-blind, sham-controlled trial with 12 youths (age range from 10 to 17 years) with schizophrenia evaluated the tolerability of tDCS.…”
Section: Tdcs In Child Psychiatrymentioning
confidence: 99%